Sophisticated investors and market efficiency: Evidence from a natural experiment - Chen, Yong; Kelly, Bryan; Wu, Wei (Journal of Financial Economics, 2020)
We study how sophisticated investors, when faced with shocks to information environment, change their information acquisition and trading behavior, and how these changes in turn affect market efficiency. We find that, after exogenous reductions of analyst coverage due to closures and mergers of brokerage firms, hedge funds scale up information acquisition, trade more aggressively, and earn higher abnormal returns on the affected stocks. The hedge fund participation also mitigates the impairment of market efficiency caused by coverage reductions. Overall, in a causal framework, our findings suggest a substitution effect between sophisticated investors and public information providers in facilitating market efficiency.